Bladder Agenesis Associated With Fused Crossed Renal Ectopia and Vertebral Anomalies- A Rare Entity - Sailo, Stephen Lalfakzuala; Sailo, Laltanpuii (Urology Journal, 2016)
A 9-months-old girl presented with dribbling of urine without normal voiding since birth. On examination, child was healthy. Abdominal examination was normal. On separating the labia, a single opening with urine leak was seen, urethral opening could not be identified. Abdominal ultrasonography showed crossed left renal ectopic kidney in the right iliac fossa and computed tomography showed normally excreting fused crossed ectopic kidneys (lump kidney),both ureters draining into a urogenital sinus, butterfly and block lumbar vertebrae. S.Creatinine was normal (0.3 mg %). Endoscopy using a paediatric cystoscope through the genital opening showed a urogenital sinus where both ureteric openings were located and both ureters were refluxing when the sinus was filled with contrast .We plan for continent diversion with cutaneous stoma.